Combustion and exhaust emissions of canola biodiesel blends in a single cylinder DI diesel engine. (August 2017) - Can, Özer; Öztürk, Erkan; Yücesu, H. Serdar
Abstract: In this study, effects of the canola biodiesel blends in 5%, 10%, 15% and 20% proportions (in vol.) with diesel fuel were investigated at four loads (4.8, 3.6, 2.4 and 1.2 bar BMEP) in a single-cylinder DI engine. Comprehensive combustion analyses showed that, although the start of injection timings were inadvertently advanced from the system response, the combustion of canola biodiesel blends generally resulted in shorter ignition delay period for all loads due to earlier combustion timing. The maximum heat release rate generally decreased gradually with the reduction of premixed combustion fractions and corresponding increase in the diffusion combustion fractions when the canola biodiesel ratio was increased. Slightly reducing the maximum in-cylinder pressures and maximum in-cylinder pressure rise rates were caused a slight retardation on the center of heat release locations and longer combustion durations. BSFC results increased up to 6.56% and BTE reduced up to 4.2% when the canola biodiesel ratio was increased to 20% at the high load. The canola biodiesel blends also resulted in higher NOx emissions of 8.9% as well as lower smoke, CO and THC but slightly higher CO2 emissions for all loads. Highlights: The detailed combustion analyses of canola biodiesel blends were performed. Canola blends resulted in the lower premixed and higher diffusion combustion fractions. Canola blends resulted in lower cylinder pressure by delaying CA50. Canola biodiesel blends resulted in higher NOx and lower smoke for all loads. Lower CO and THC emissions with higher CO2 were observed for all loads.